Pembelajaran Kontekstual dalam Meningkatkan Keterampilan Berhitung Anak Usia Dini - Annisak, Annisak (Jurnal I TIBAR, 2024)
Early Childhood Education is an important foundation in shaping their cognitive, social and emotional development. In this domain, developing numeracy skills is one of the main focuses, because it has a significant impact. One approach that has attracted attention in improving numeracy learning in early childhood is the contextual learning approach. The research used is a qualitative descriptive approach using the Miles and Huberman approach, namely data reduction, data presentation and drawing conclusions. This research was carried out at KB Al-Farah Seri Kembang III. The children studied were aged 3-4 years. Based on the results of researchers' observations on children aged 3-4 years, children's cognitive development through contextual-based learning. The results of the analysis show that the percentage value for observing teacher and student activities in cycle I was 45.90% and increased in cycle II to 85.26%. These results show the suitability of the data received. Thus, it can be stated that contextual learning through the implementation of block media in the al-farah series kembang III can improve the numeracy skills of young children aged 3-4 years.